Developmental potential of non- and mono-pronuclear zygotes and associated clinical outcomes in IVF cycles - Zhu, Mengyi; Dong, Qiyin; Zhu, Yurong; Le, Yun; Wang, Tengfei; Zhou, Yuanping; Yang, Sheng (Frontiers in Endocrinology, 2024)
Purpose This study aims to evaluate the developmental potential of 0PN, 1PN, and 2PN zygotes in IVF cycles and compare their clinical outcomes. Methods We conducted a retrospective cohort study involving IVF patients. Blastocyst formation rates were assessed with 0PN, 1PN, and 2PN zygotes. Subsequently, we collected clinical outcome data following the transfer of these zygotes. Results The overall blastulation rate was similar between 0PN (29.6%) and 2PN (32.1%) zygotes, but 1PN zygotes exhibited a significantly lower blastulation rate (17.0%) compared to both 0PN and 2PN zygotes. Similarly, the overall rate of good-quality blastulation was comparable between 0PN (15.3%) and 2PN (17.5%) zygotes, while 1PN zygotes showed a significantly lower rate (7.0%) compared to both 0PN and 2PN. Clinical pregnancy, ectopic pregnancy, implantation, and live birth rates were similar among single blastocyst frozen embryo transfers (FET) of 0PN, 1PN, and 2PN. Additionally, no significant differences were observed between single- and double-blastocyst FET of 0PN and 2PN. Conclusions Our findings suggest that 0PN and 2PN zygotes have comparable developmental potential, while 1PN embryos exhibit lower developmental potential. Blastocyst FET outcomes appear similar among 0PN, 1PN, and 2PN zygotes.